O-1 Developing a 'voice for volunteering' – the EAPC madrid charter on volunteering. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Scott, Ros; Pelttari, Leena
Abstract : Background: The perception of hospice and palliative care (HPC) volunteers as willing amateurs, peripheral to the multi-disciplinary team overlooks the importance and complexity of their work in delivering truly holistic care. This project, led by the European Association for Palliative Care (EAPC) Task Force on Volunteering aimed to develop a volunteering charter. Aims: The aims were to develop a Charter to: Promote the successful development of volunteering. Recognise volunteering as a third resource. Promote research and best practice models. Methods: Information was initially collected during an international HPC volunteering symposium in Prague in 2013. Further feedback on draft versions was gathered at international congresses in (Vienna & Copenhagen, 2015; Dublin, 2016). Additionally, email consultation took place with researchers, volunteers, staff, and EAPC Board members. Thirteen countries (Australia, Austria, Belgium, Croatia, Germany, Hungary, Ireland, Italy, The Netherlands, Poland, Portugal, Romania, and UK) took part in the consultation process. Results: Consensus was reached and a Charter developed with goals for individuals, organisations and national organisations, focused on four key themes: 1) Recognise the important role of volunteers in the total care of patients and their families, and in sustaining HPC services. 2) Promote volunteering in support of patients and their families. 3) Ensure effective management of volunteering, including clearly defined policy on roles, careful recruitment, selection, training and development. 4) Ensure effective support for hospice and palliative care volunteering at organisational, local and national levels. The Charter was adopted by the EAPC Board and launched as an official EAPC Charter at the EAPC World Congress in Madrid in 2017. Conclusions: This project was successful in creating a Charter with a consensus about the importance and place of volunteering in HPC. This next stage is to evaluate the implementation and impact of the Charter over the next two years.